Application of Cantor pairing function in the two simplest tasks - Zhetpisov, K.; Tynyshtykbaiy, K.; Kusbekov, Sh.D. (Ye.A.Buketov Karaganda State University Publishing house, 2014)
In this paper application of Cantor pairing function is considered in solving the following two problems. 1. In determining the main Pythagorean triples. 2. When calculating the sum of the digits of n-digit numbers in the decimal number system. When calculating the sum of digits of all unequivocal to n-digit numbers in the decimal number system. For these two problems program was written in the programming language Borland Delphi 7.
Канторлық номерлерді қарапайым екі есепті шешуде қолдану
Применение канторовской нумерации в двух простейших задачах
Keywords: Diophantine equation; Pythagorean equation; Pythagorean triple; Cantor pairing function; tuple; linear order; Cantor’s number